General Principles and Challenges of Public Administration Organization in Hungary - Kálmán, János; Hulkó, Gábor (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
The organization of administrative bodies in Hungary has undergone significant changes over the past decades. After the change of regime, the basic democratic rules of the state were introduced, which also fundamentally determined the system of public administration. These influences led to the development of the constitutional basis for the system of public administration, which has evolved steadily since the change of regime. An important milestone in the regulation of the organization of public administration was the new Fundamental Law of 2011, which laid the foundations for several conceptual changes. The present chapter provides a textbook overview of the basic geographical characteristics of Hungary, the basic constitutional rules governing the public administration system, and the public administration system, specially focusing on state administration and local governments. The focus is on public administration bodies and their organization, with the chapter outlining also the current challenges faced by the organization of public administration in Hungary and predicaments for its future development.KEYWORDS Hungary, public administration, public administration bodies, constitutional principles, principles of public administration, local self-governmentsBibliographyBarta, A. (2012) ‘A területi államigazgatás változásai az elmúlt húsz évben’, Új Magyar Közigazgatás, 5(2), pp. 3–10.Barta, A. (2021) ‘Fővárosi és megyei kormányhivatalok. Egy évtized margójára’, KözigazgatásTudomány, 1(2), pp. 4–15 [Online]. Available at: https://doi.org/10.54200/kt.v1i2.12 (Accessed: 12 February 2024).Borsa, D., Hulkó, G., Király, P. B., Pardavi, L. (2022) ‘A települési adók szabályozási környezete, gyakorlata és kihívásai: Van-e jelentősége a települési adónak krízishelyzetekben vagy egyáltalán?’, KözigazgatásTudomány, 2(2), pp. 22–34 [Online]. Available at: https://doi.org/10.54200/kt.v2i2.44 (Accessed: 12 February 2024).Csörgits, L., Gyurita, E.R., Hulkó, G., Kálmán, J., Lapsánszky, A. (2020) A közigazgatási jog elmélete és gyakorlata. Győr: Universitas-Győr Nonprofit Kft.Fazekas, J. (2015) ‘Az önálló szabályozó szervek rendeletalkotási tevékenysége Magyarországon’, Új Magyar Közigazgatás, 8(2), pp. 15–20.Fábián, A., Hoffman, I. (2014) Az államigazgatási területi és helyi szervei: kormányhivatalok, járási intézmények. Budapest: NKE.Franczel, R. (2013) ‘A miniszterelnök alaptörvényi szabályozása’, Jog Állam Politika, 5(2), pp. 17–44.Gyurita, R. (2014) ‘A fővárosi és megyei kormányhivatal’, Új Magyar Közigazgatás, 7(2), pp. 8–19.Gyurita, R. (2021) ‘Integrációs folyamatok a területi államigazgatási szervezetben, a fővárosi és megyei kormányhivatalok’, KözigazgatásTudomány, 1(2), pp. 54–73 [Online]. Available at: https://doi.org/10.54200/kt.v1i2.16 (Accessed: 12 February 2024).Hoffman, I. (2021) ‘Opportunities for central (regional) government to intervene in decisions and operations of local governments in Hungary’, Institutiones Administrationis – Journal of Administrative Sciences, 1(1), pp. 30–39 [Online]. Available at: https://doi.org/10.54201/iajas.v1i1.6 (Accessed: 12 February 2024)Hulkó, G., Kálmán, J. (2013) ‘Autonóm struktúrák Magyarország és a Cseh Köztársaság államigazgatásában’, Új Magyar Közigazgatás, 6(10), pp. 1–8.Józsa, Z. (2019) ‘A közigazgatás funkciói és feladatai’, Internetes Jogtudományi Enciklopédia [Online]. Available at: http://ijoten.hu/szocikk/a-kozigazgatas-funkcioi-es-feladatai (Accessed: 12 February 2024).Kálmán, J. (2018) ‘A területi államigazgatás’ in Kálmán, J., Lapsánszky, A. (eds.) Közigazgatási jogi alapismeretek. Győr: Universitas-Győr, pp. 73–91. Kálmán, J. (2021) ‘Az önálló szabályozó szervek jogállása, helyük az államigazgatás szervrendszerében’, KözigazgatásTudomány, 1(2), pp. 74–85 [Online]. Available at: https://doi.org/10.54200/kt.v1i2.17 (Accessed: 12 February 2024). Kálmán, J. (2023) ‘The legal status of independent regulatory organs and their place in the system of Hungarian public administration’, Public Governance, Administration and Finances Law Review, 8(1), pp. 105–119 [Online]. Available at: https://doi.org/10.53116/pgaflr.6561 (Accessed: 12 February 2024). Kálmán, J., Lapsánszky, A. (eds.) (2017) Közigazgatási jogi alapismeretek. Győr: Universitas-Győr Nonprofit Kft. Lapsánszky, A., Patyi, A., Takács, A. (2017) A közigazgatás szervezete és szervezeti joga. Budapest: Dialóg Campus Lentner, Cs., Hegedűs, S. (2022) ‘The Development History and Economic Characteristics of the Hungarian Local Tax System from the Change of the Regime until the Pandemic’, Institutiones Administrationis – Journal of Administrative Sciences, 2(2), pp. 46–60 [Online]. Available at: https://doi.org/10.54201/iajas.v2i2.53 (Accessed: 12 February 2024). Nagy, S. (2023) ‘Önkormányzati autonómia – alkotmányos alapjog vagy személyiségi jog?’, KözigazgatásTudomány, 3(1), pp. 154–170 [Online]. Available at: https://doi.org/10.54200/kt.v3i1.54 (Accessed: 12 February 2024) Patyi, A. (2017) A közigazgatási működés jogi alapjai. Budapest: Dialóg Campus. Patyi, A., Rixer, Á. (eds.) (2014) Hungarian public administration and administrative law. 1st edn. Passau: Schenk Verlag. Patyi, A., Varga, Zs. A. (2019) A közigazgatási eljárásjog alapjai és alapelvei. Budapest: Dialóg Campus.  Petrétei, J. (2014) Magyarország alkotmányjoga II. Államszervezet. Pécs: Kodifikátor Alapítvány. Rámhápné Radics, K. A. (2023) ‘Helyi önkormányzati autonómia: mi változik, mi marad?’, Közigazgatás Tudomány, 3(1), pp. 85–98 [Online]. Available at: https://doi.org/10.54200/kt.v3i1.50 (Accessed: 12 February 2024). Rozsnyai, K. (2017) ‘A közigazgatás fogalma’ in Fazekas, M. (eds.) Közigazgatási jog. Általános rész I.: A közigazgatásról általában. Közigazgatási szervezeti jog. Közszolgálati jog. 1st edn.Budapest: ELTE Eötvös Kiadó, pp. 21–35. Stumpf, I. (2015) ‘A kormány alkotmányos jogállása’, Új Magyar Közigazgatás, 8(2), pp. 8–10. Tamás, A. (1994) Public Administration Law I. Miskolc: JATEPress. Torma, A., Czékmann, Zs., Nyitrai, P., Szabó, B., Ritó, E., Czibrik, E., Cseh, G. (2022) ‘Gondolatok a magyar közigazgatási stratégiaalkotásról, különös tekintettel a központi szervekre’, PRO PUBLICO BONO: MAGYAR KÖZIGAZGATÁS, 10(1), pp. 46–64 [Online]. Available at: https://doi.org/10.32575/ppb.2022.1.3 (Accessed: 12 Februar y 2024). Vadál, I. (2006) A közigazgatási jog kodifikációja. Budapest: Dialóg Campus. Varga, Á. (2023) ‘Thoughts on the meaning content of the principle of local autonomy’, Institutiones Administrationis – Journal of Administrative Sciences, 3(1), pp. 85–97 [Online]. Available at: https://doi.org/10.54201/iajas.v3i1.65 (Accessed: 12 February 2024).